Ajuste para edad y peso en producción de leche en criollo centroamericano - Meini Sponza, G. (IICA, San José (Costa Rica) CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag. Sc.) -- IICA, San José Costa Rica), 1973